Efficacy and safety of ezetimibe and ezetimibe plus statin therapy in patients aged under 65, 65––74 and 75 years and older. (December 2007) - Robinson, Jennifer G; Davidson, Michael H; Shah, Arvind; Lin, Jianxin; Neff, David; DeLucca, Paul T; Tomassini, Joanne E; Veltri, Enrico; Tershakovec, Andrew M
Although the greatest burden of cardiovascular disease occurs after age 65 years, limited efficacy and safety data are available for cholesterol-lowering drugs in elderly patients. We undertook a pooled analysis of individual data from 13, 282 patients aged 18––93 years in 16 published trials of ezetimibe and ezetimibe added on to or coadministered with a statin (ezetimibe/statin). Overall, ezetimibe reduced low-density lipoprotein cholesterol by 20% compared with placebo and ezetimibe/statin reduced low-density lipoprotein cholesterol by 17% compared with a statin alone, with consistent treatment effects across age groups (<65, 65––74 and ≥≥75 years). Rates of any adverse or drug-related adverse events were also similar across age groups. We conclude that the lipid efficacy and safety of ezetimibe and ezetimibe/statin in those aged 65––74 and 75 years and older are similar to those observed in patients aged under 65 years.